Investigation of Aryl Isonitrile Compounds with Potent, Broad-spectrum Antifungal Activity - Mohammad, Haroon (Bioorg Med Chem, 2017)
Invasive fungal infections present a formidable global public health challenge due to the limited number of approved antifungal agents and the emergence of resistance to the frontline treatment options, such as fluconazole. Three fungal pathogens of significant concern are Candida, Cryptococcus, and Aspergillus given their propensity to cause opportunistic infections in immunocompromised individuals. New antifungal agents composed of unique chemical scaffolds are needed to address this public health challenge. The present study examines the structure-activity relationship of a set of aryl isonitrile compounds that possess broad-spectrum antifungal activity primarily against species of Candida and Cryptococcus. The most potent derivatives are capable of inhibiting growth of these key pathogens at concentrations as low as 0.5 μM. Remarkably, the most active compounds exhibit an excellent safety profile and are nontoxic to mammalian cells even at concentrations up to 256 μM. The present study lays the foundation for further investigation of aryl isonitrile compounds as a new class of antifungal agents.